2007
DOI: 10.1021/pr060690r
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Neuropeptide Extraction from the Mouse Hypothalamus

Abstract: Sample preparation for neuropeptidomic studies is a critical issue since protein degradation can produce high levels of peptides that obscure the endogenous neuropeptides. We compared different extraction conditions for the recovery of neuropeptides and the formation of protein breakdown fragments from mouse hypothalami. Sonication and heating in water (70 degrees C for 20 min) followed by cold acid and centrifugation enabled the efficient extraction of many neuropeptides without the formation of protein degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 42 publications
2
79
0
2
Order By: Relevance
“…2B. These two cerebellin forms were previously identified from mouse hypothalamus studies (8); however, References found in SCN studies were for the prohormones, which were previously reported in the studies. there was no report localizing these peptides to the SCN.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…2B. These two cerebellin forms were previously identified from mouse hypothalamus studies (8); however, References found in SCN studies were for the prohormones, which were previously reported in the studies. there was no report localizing these peptides to the SCN.…”
Section: Resultsmentioning
confidence: 79%
“…Mass spectrometry, a rapid and sensitive method that has been used for the analysis of complex biological samples, can detect and identify the precise forms of neuropeptides without prior knowledge of peptide identity, with these approaches making up the field of peptidomics (7)(8)(9)(10)(11)(12). The direct tissue and single neuron analysis by MALDI MS has enabled the discovery of hundreds of neuropeptides in the last decade, and the neuronal homogenate analysis by fractionation and subsequent ESI or MALDI MS has yielded an equivalent number of new brain peptides (5).…”
mentioning
confidence: 99%
“…Peptidomics-Peptides were extracted from whole mouse brain (minus the olfactory bulb and cerebellum) as described (19,20). In brief, four mice (C57B6/J, 2-3 months old) were sacrificed by decapitation, and the head was immediately irradiated in a conventional microwave oven for 8 s to raise the brain temperature to 80°C and inactivate proteases that can rapidly degrade cellular proteins during postmortem processing of the tissue (21).…”
Section: Methodsmentioning
confidence: 99%
“…The labeling procedure has been previously described in detail (35,36). In brief, each group of cells within an experiment was labeled with one of the isotopic TMAB-Nhydroxysuccinimide labels.…”
Section: Isotopic Labeling and Mass Spectrometry For Peptide Identifimentioning
confidence: 99%